2020
DOI: 10.2215/cjn.09170819
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Deceased Donor Kidney Procurement Biopsies

Abstract: Background and objectivesUnfavorable histology on procurement biopsies is the most common reason for deceased donor kidney discard. We sought to assess the reproducibility of procurement biopsy findings.Design, setting, participants, & measurementsWe compiled a continuous cohort of deceased donor kidneys transplanted at our institution from 1/1/2006 to 12/31/2016 that had at least one procurement biopsy performed, and excluded cases with missing biopsy reports and those used in multiorgan transplants. Subo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…For each of these histologic parameters, we used the previously validated scoring system that assigns a score of 0 (most favorable) to 3 (least favorable) consistent with thresholds from prior studies using this cohort (Table 1). 10 In cases in which a range of values was reported for any compartment, the lower end of the range was used to assign the histologic score (e.g. "moderate to severe" vascular disease was scored as 2).…”
Section: Procurement Biopsy Results and Scoringmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of these histologic parameters, we used the previously validated scoring system that assigns a score of 0 (most favorable) to 3 (least favorable) consistent with thresholds from prior studies using this cohort (Table 1). 10 In cases in which a range of values was reported for any compartment, the lower end of the range was used to assign the histologic score (e.g. "moderate to severe" vascular disease was scored as 2).…”
Section: Procurement Biopsy Results and Scoringmentioning
confidence: 99%
“…However, several previous studies have demonstrated that-unlike high-quality reperfusion biopsies-procurement biopsies are typically poorly reproducible, not reflective of the gold-standard histology to which clinicians are accustomed, and, as a result, poorly predictive of posttransplantation outcomes. 11À17 However, although procurement biopsy findings overall are not associated with allograft outcomes, we recently showed that procurement biopsies performed by a specific organ procurement organization are associated with posttransplantation outcomes, 10 leading to our hypothesis that certain practice pattern variations, such as tissue sampling technique and the prior training of the interpreting pathologist, underlie this finding through their influence on the accuracy of procurement biopsy findings. However, in this study, we found that neither core versus wedge sampling nor the level of renal pathology expertise of the interpreting pathologist was associated with a higher likelihood of accuracy of procurement histology compared to gold-standard reperfusion histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously provided solid evidence that a preimplantation histologic score defined based on validated criteria predicts short- and long-term outcomes of kidneys from older/marginal donors preserved with CS [9, 10]. However, this has not been a uniform finding across groups [40, 41], possibly because biopsy scoring has not always been performed by ad hoc trained kidney pathologists on optimally processed samples [39, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy findings are a common reason for kidney turndowns 6 . Biopsy findings are inconsistent when read by on‐call pathologists and not necessarily a reliable indicator of later function or graft survival 8‐10 . When evaluated by trained renal pathologists, showed donor pre‐existing damage was an independent predictor of 12‐month renal function and outcome evaluated by a composite variable including death‐censored graft survival and time to reach an estimated glomerular filtration rate <30 ml/min .…”
Section: Introductionmentioning
confidence: 99%